Microalgae: potential source of third generation biofuel - Sharma, Gulshan Kumar; Dev, Rahul; Daya, Devi (Indian Farming, 2018)
Algae is highly productive third generation biofuel, contains high amount of lipids compared to oil yielding crop plants. Algae biomass has a vast potential in production of several biofuels as Biodiesel, Biogas, Bioethanol, Biohydrogen apart from that algal fuel has several social and environment benefits compared to conventional fuels. But biodiesel from microalgae still has not yet become economical, hence require a future research on economical industrial scale production of algal biofuels with lower cost.